Mental health impact on at-risk high-level athletes during COVID-19 lockdown: A pre-, during and post-lockdown longitudinal cohort study of adjustment disorder - Simons, C.; Martin, L. A.; Balcombe, L.; Dunn, P. K.; Clark, R. A. (Journal of Science and Medicine in Sport, 2021)
We read with great interest the July issue of the Journal of Science and Medicine in Sport regarding the impact of the COVID-19 pandemic on athletes. In that issue, Pillay et al. reported that 52% of athletes felt depressed during the lockdown period. There is, however, a lack of baseline data hindering the comparison of these findings to the pre-pandemic prevalence. This prompted us to do an early analysis of our ongoing longitudinal cohort study examining Adjustment Disorder (AjD) in Australian high-level athletes. AjD is a stress-response syndrome centred around preoccupation with a stressor (e.g. constant ruminations), and the failure to adapt to the stressor. AjD is often accompanied by symptoms of depression, anxiety, impulsivity and avoidance. High-level athletes possess proportionally high levels of mental health issues and may be susceptible to AjD. AjD may be exacerbated by the pandemic ; uncertainty about competitions, qualification procedures (e.g. for the Olympics) and training environment restrictions may cause athletes stress in addition to the pandemic itself. Many high-level athletes also face disruptions to study, job loss and subsequent decreased income, further increasing their risk of suffering mental health issues. Our study was originally designed to monitor high-level athletes during a period of adjustment to a specific stressor (injury, relocation, or being on tour/long periods away from home), indicating they were an at-risk group. Importantly, our dataset contains continuous, longitudinal AjD information recorded prior to, throughout, and after the first wave of COVID-19 and lockdown restrictions in Queensland, Australia.